Humification and Humic Acid Composition of Suspended Soil in Oligotrophous Environments in South Vietnam - E. V. Abakumov; O. A. Rodina; A. K. Eskov (Applied and Environmental Soil Science)
Humification is considered to be a global process that is implemented in soils and organic sediments and also in natural water and air. The term “suspended soils” has become increasingly common in recent years. Suspended soils are defined as the part of the organic matter that has not undergone the full decomposition process and has not turned into the humus of terrestrial soils. Suspended soils were shown to contain higher total nitrogen, phosphorus, and potassium contents than the forest soil, but the moisture content in suspended soils was significantly lower. Our study of the structural composition of humic substances in suspended soils was conducted with an aim of evaluating the humification rates and structural composition of humic acids in the suspended soil in tropical forests of South Vietnam. Soil samples from three selected areas were investigated: the soil under phorophytes (mineral soil presented by samples of topsoil of the typical dry savanna landscape) and two soils from epiphytous formations. Samples were collected from savanna-type sparse communities, located on oligotrophous plains in Phú Quốc Island (South Vietnam) in 2015. General properties of the soil and the elemental composition of suspended soils were determined, and the humic substance chemical composition was evaluated using solid state 13C-NMR. Data obtained showed that the pH of the soils under phorophytes was higher than in the suspended soils; basal respiration did not tend to change indices between soils under phorophytes and suspended soils, but the suspended soil was less enriched by nitrogen than the soil under phorophytes. This can be related to the total amount of organic matter exposed to humification in various soils and to the presence of an essential portion of mineral particles in the soil under phorophytes. Data on elemental composition of the humic acids (HAs) indicated that one method of humification is implemented in all three soils that were investigated. The humic acids of the phorophyte soil showed the same content of aromatic fraction as the suspended soil. The most comparable soil type in terms of humic substance composition is Cambisols from humid forests of subboreal and subtropical zones. The humification process implemented in suspended soils showed the absence of mineral compounds or mineral fine earth, which indicated that humification in conditions of pure organic substrates can result in formation of deep humified organic matter, as shown by humic acids with an essential aromatic fraction content.